Facile preparation of a phenolic aerogel with excellent flexibility for thermal insulation. (15th January 2022) - He, Han; Geng, Liyan; Liu, Feng; Ma, Bin; Huang, Wenxuan; Qu, Lijie; Xu, Baosheng
Graphical abstract: Highlights: A facile preparation method of flexible phenolic aerogel was reported. Commercial resins and ambient pressure drying can reduce preparation period. The FPA possesses low thermal conductivity, excellent compressibility. Abstract: An ambient pressure drying, cost-effective and environment-friendly synthesis method for aerogels has been continuously pursued by scholars. However, phenolic aerogels are usually rigid and prepared from phenol and aldehyde monomers through complicated and long-time supercritical drying processes, which limit their production efficiency. This paper introduces an ambient pressure drying method for preparing lightweight and low-thermal-conductivity phenolic aerogels with excellent flexibility. The prepared flexible phenolic aerogels (FPAs) have a complete 3D network structure, low thermal conductivity (approximately 0.03 W/(m·K)) and excellent compressibility and recovery performance (compression strain can reach 50%, and rebound rate can reach 80%). Given their simple synthesis, simple scaling up and excellent mechanical properties, such flexible phenolic aerogels may have great potential to serve as thermal insulating materials.